The productivity-wage premium. Does size still matter in a service economy? - Berlingieri, Giuseppe; Calligaris, Sara; Criscuolo, Chiara (Paris, 2018)
"The literature has established two robust stylised facts: (i) the existence of a firm size-wage premium; and (ii) a positive relationship between firm size and productivity. However, the existing evidence is mainly based on manufacturing data only. With manufacturing nowadays accounting for a small share of the economy, whether productivity, size, and wages are closely linked, and how tight this link is across sectors, is still an open question. Using a unique micro-aggregated dataset covering the whole economy in 17 countries over 1994-2012, this paper compares these relationships across sectors. While the size-wage and size-productivity premia are significantly weaker in market services compared to manufacturing, the link between wages and productivity is stronger. The combination of these results suggests that, in a service economy the “size-wage premium” becomes more a “productivity-wage premium”. These results have first-order policy implications for both workers and firms."